2021
DOI: 10.1002/capr.12465
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of university students' experience of Internet‐based CBT for depression

Abstract: Growing interest in the potential use of digital technologies, including Internet-based treatments and smart phone applications, to deliver treatments for common mental disorders has resulted in rapid expansions in the availability and utilisation of digital mental health interventions (Hill et al., 2017). There is an ever-growing range of digital mental health interventions available including mobile applications, such as Headspace and MoodyMe (Flett et al., 2020); self-guided and guided Internet-based interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 77 publications
2
22
0
Order By: Relevance
“…Self-guided DMHIs are considered to have the highest potential in terms of cost-effectiveness and scalability ( Muñoz et al, 2015 ) whereas guided DMHIs have been observed to fare better in terms of clinical efficacy and engagement ( Grist et al, 2019 ; Karyotaki et al, 2021 ; Baumeister et al, 2014 ), and stakeholder acceptance ( Davies et al, 2020 ; Topooco et al, 2017 ). The finding of students' interest in DMHIs with human support is in line with previously reported findings, which have included preference among stakeholders for in-person therapy and blended treatments (combination of sessions and self-help) over guided ICBT programs ( Davies et al, 2020 ; Topooco et al, 2017 ; Peynenburg et al, 2020 ; Lokkerbol et al, 2019 ; Gericke et al, 2021 ). In our study we did not categorize and directly compare DMHIs based on guidance/self-help so as not to introduce bias in students' reflections on them.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Self-guided DMHIs are considered to have the highest potential in terms of cost-effectiveness and scalability ( Muñoz et al, 2015 ) whereas guided DMHIs have been observed to fare better in terms of clinical efficacy and engagement ( Grist et al, 2019 ; Karyotaki et al, 2021 ; Baumeister et al, 2014 ), and stakeholder acceptance ( Davies et al, 2020 ; Topooco et al, 2017 ). The finding of students' interest in DMHIs with human support is in line with previously reported findings, which have included preference among stakeholders for in-person therapy and blended treatments (combination of sessions and self-help) over guided ICBT programs ( Davies et al, 2020 ; Topooco et al, 2017 ; Peynenburg et al, 2020 ; Lokkerbol et al, 2019 ; Gericke et al, 2021 ). In our study we did not categorize and directly compare DMHIs based on guidance/self-help so as not to introduce bias in students' reflections on them.…”
Section: Discussionsupporting
confidence: 91%
“…Although they noted that the DMHI may be convenient and accessible they compared it with in-person therapy and counseling services and expected it to be impersonal or possibly not as supportive (Online suppl.). Gericke and colleagues recently found similar views among South African students based on first-hand experiences with this type of DMHI ( Gericke et al, 2021 ).…”
Section: Discussionmentioning
confidence: 68%
“…Two further articles demonstrate value in shaping policies and services that involve the views and experiences of students and staff, including the following: (1) students' experiences of Internet-based treatment for depression for tackling moderate-to-severe depression (Gericke et al, 2021); and (2) therapists' insight into offering counselling in universities in Ireland and highlighting the complexity of working flexibly and creatively to respond to students' evolving needs (Harrison & Gordon, 2021). Three final articles in this special section employ methods that generate large data sets across broad student populations and argue for these data to shape clinical services, including the following:…”
Section: Con Clus Ionmentioning
confidence: 99%
“…A metaversity is a higher education institution reconstructed as a digital twin in the metaverse using virtual reality (or at least the early iteration of what will ultimately become a full, global metaverse) [41]. Creating a metaversity entails creating a digital campus that mimics the physical campus [42]- [47]. Certain metaverses are presently operational, as contrast to the general metaverse, which is simply a theoretical idea.…”
Section: Introductionmentioning
confidence: 99%